Pengembangan Handout Digital Berbasis Aplikasi Ibis Paint X Pada Materi Pembuatan Desain Busana - Malinda Ayu Dewi; Imami Arum Tri Rahayu; Ma’rifatun Nashikhah; Mita Yuniati (Jurnal Bintang Pendidikan Indonesia, 2024)
One of the roles of technology in learning activities is to make it easier for teachers and students to access various educational resources. Technology integration in learning activities is a planned activity of using or combining technology in classroom learning activities to improve the quality of the learning process.In the era of digital transformation, conventional learning media became less practical to use. For instance, when learning how to make fashion designs, there were not many digital handouts available to study the use of drawing applications for learning activities to create fashion designs. To address this gap, this research aims to develop digital handouts based on Ibis Paint X. The research follows the ADDIE research design as part of its research and development (R&D) process. The results of the feasibility test by two media validators obtains an average score of 86.25% with very feasible criteria. The results of the feasibility test by two material validators obtains an average score of 95% with very feasible criteria. Based on the research results, it can be concluded that the digital handouts developed are very suitable for use in learning to make fashion designs.